Methods for the study of marine benthos (Blackwell Science, 2005)
Ecosystems of the benthic environment are a sensitive index to ecological change, and as such demand long-term and effective monitoring. Methods for the Study of Marine Benthos provides comprehensive information on the tools and techniques available to those working in areas where the declining health of the sea, depletion of marine resources and the biodiversity of marine life are major concerns.